Panic buying and consumption displacement during COVID-19: Evidence from New Zealand - Colin Michael Hall; Peter Fieger; Girish Prayag; David Dyason (Economies, 2021)
Panic buying and hoarding behavior is a significant component of crisis- and disaster-related consumption displacement that has received considerable attention during the COVID-19 pandemic. Understanding such purchasing and stockpiling behavior provides critical information for government, disaster managers and the retail sector, as well as policy makers to adjust crisis response strategies and to better understand disaster management, including preparedness and response strategies. This study examines consumer purchasing behavior, retail spending and transactional data for different retail sectors between January 2017 and December 2020 using data for the greater Christchurch region in New Zealand. Once COVID-19-related panic buying began, overall spending increased sharply in anticipation of lockdowns. Transactional spending increased and subsided only slowly to a level higher than pre lockdown. The magnitude of the panic buying event far exceeded historical seasonal patterns of consumer spending outside of Christmas, Easter and Black Friday, although daily spending levels were comparable to such consumption events. The results of the study highlight the importance of comparing panic buying to other events in terms of purchasing motivations and also considering that so-called panic buying may contribute to greater individual and household resilience. The volume of sales alone is not adequate to define panic buying. Instead, the extent of divergence from the normal daily spending value per retail transaction of a given population provides a much more accurate characteristic of panic buying.
Keywords: 330; COVID-19; displacement; panic-buying; retail spending; stockpiling